Stimuli‐Responsive MXene/PNIPAM Hydrogel WITH High‐Performance and Tunable Electromagnetic Interference Shielding Performance - Qian Yan; Zonglin Liu; Jinhua Xiong; Huanxin Lian; He Chen; Teng Fei; Yunxiang Chen; Haowen Zheng; Xu Zhao; Liangliang Xu; Fuhua Xue; Yesheng Zhong; et al. (Advanced Science)
Abstract Smart electromagnetic interference (EMI) shielding materials capable of reversible EMI response hold great promise for application in flexible electromagnetic devices. Here, PPM hydrogels composed of poly (N‐isopropylacrylamide) (PNIPAM) and MXene/PEDOT: PSS hybrid fillers are fabricated via ice‐templated freeze‐in‐situ polymerization. The anisotropic structural design of the hydrogel enhances its mechanical properties, conductivity, and EMI shielding properties in a specific direction. Furthermore, it can rapidly adjust its internal water content under thermal and light stimulation. The EMI shielding performance of PPM hydrogels can transition from an EMI shielding status (EMI shielding on, >50 dB) to an EM‐wave‐transparent status (EMI shielding off, ≈2 dB) in the X‐band with the dynamic change in water content. Notably, the EMI SE value of PPM hydrogel in the X‐band can be quantitatively adjusted from ≈59.3 to 15.5 dB, demonstrating excellent repeatability and adjustability. A real‐time electrical switching capability in the broad GHz frequency range (8.2–40 GHz) is achieved through dual stimuli‐responsive (temperature‐responsive and light‐responsive) modulation. This study presents a new model for dynamically switchable EMI shielding and reveals the great application potential of smart on/off switchable hydrogel‐based EMI shielding materials as next‐generation multifunctional electronics.